ANALISIS POTENSI DAERAH PULAU-PULAU TERPENCIL DALAM RANGKA MENINGKATKAN KETAHANAN, KEAMANAN NASIONAL, DAN KEUTUHAN WILAYAH NKRI DI NUNUKAN–KALIMANTAN TIMUR - Chairil N. Siregar (Jurnal Sosioteknologi, 2008)
Indonesia is the biggest archipelago country. Unfortunately, the result of national development has not yet evenly distributed to remote islands along the borderlines. To find out the cause, a qualitative research should be conducted. It focuses on the local potentials, economic condition, socio-culture, local wisdom, and national defense. The result of this study shows the potentials of Nunukan and Sebatik Regency are agroindustry (plantation and forestry), oceanography, international trade, mining, port service, and tourism. The economic condition of Nunukan Society is developed enough, while Sebatik is still left behind. Their employement includes trading, gardening, fishing, farming, private and civil service. The socio-culture condition consists of various ethnics such as Dayak, Tedung, Bugis, Jawa, and Nusa Tenggara Timur (NTT). Those areas are open for newcomers. The local wisdom refers to traditionally managing natural resources. Their nationalism is strong enough and none becomes Askar Wataniah. The security issues that needs more attention include illegal logging, fish theft, robbery on sea, drug abuse, and illegal tresspassing.